Program Peningkatan Resilience pada Orang Tua yang Memiliki Anak Pecandu Narkoba - Suhana Suhana (SCHEMA (Journal of Psychological Research), 2019)
S u h a n a. Curriculum design to improve parent Resilience with drugs abuser children (case study for parents with drugs abuser children in Inabah Suryalaya boarding school Tasikmalaya). Children is the greatest of gift for all parents, if the children sick, parent will arxious and doing things to make batter for the children, parents will also feel very proud if the children succeed. Now a days, drugs is threatening tenage and adults. Base on new fact from BNN, the last five years the use of drugs improving 3617 in 2001 become 17355 in 2005 or 34,4% per year or 20 case each day. The death of drugs abuser 15 about 41 people dies each day or almoust 2 people dies in each hour. It is not easy to have children who have drugs problem. The parents need to have resilience in dealing with adversity from the problem. The research question is " what kind of effective curriculum design to enhance parents resilience with drugs abuser children ?". The research subject is 5 parents who meets cnteria In order to answer the question, the research divide inti three activrty : I st activity is the measurement of resilience acmed to discover resilience is profile of thr subject through interview and quesionaire baout resilience from Karen Reivich and Andrew Shatte (2002) base on 7 skilis. 2nd activity is assessment in risks factors and the results is the percentage from the risks factor that influence parents resilience as the research subject 3rd activity, designing curriculum to enhance the resilience. The rcsult base from 2nd activity is the low resilience, causing by high level of anxiety in subject. Base on this fact the curriculum design is base on cognitive approach. Rational-Emotive Theraphy from Atbert Ellis is the basic theory to design curriculum. The second highest risk is the parents have less knowladge about the children shengh and weakness also dont have enough knowladge about addiction, because of this fact that's the curriculum is aimed to improve parents skill through active listening.